Reproduction ecology of an emerging fishery resource, the amphibious mudskipper Periophthalmus chrysospilos, in the Mekong Delta - Quang Minh Dinh; Ton Huu Duc Nguyen; Tran Thi Huyen Lam; Ngon Trong Truong; Tien Thi Kieu Nguyen; Zeehan Jaafar (Ecology and Evolution, 2022)
Abstract Populations of Periophthalmus chrysospilos, the Gold‐spotted mudskipper, within the Mekong Delta are facing extirpation risks due to indiscriminate harvesting for the growing aquarium and food‐fish trade. This study provides some of the first information on reproductive ecology—such as spawning type and season, length at first maturity, and batch fecundity—of this species, to be used in their management. The sex ratio of wild populations, based on 1031 individuals (523 males and 508 females) is 1:1. The gonadosomatic index (GSI) values are exhibit a non‐normal distribution and changed with gender, season, and site. A combination of GSIs and the monthly appearance of mature gonads suggest that this species reproduces throughout the year, with peak from July to October. This species exhibits sexual and spatial variation in size at first maturity (Lm) as Lm is 6.2–8.6 cm in males and 6.4–7.3 cm in females. The batch fecundity (F = 2614 to 23,465 eggs/female) exhibits non‐normal distribution and varies with site, with the highest values at Dam Doi, Ca Mau (13,336 ± 1,279 SE) and the lowest at Tran De, Soc Trang (6654 ± 851 SE). In addition, batch fecundity is directly proportional to body size due to high determination relationships between batch fecundity and fish size (r2 > 0.64 for all cases). Information derived on the reproductive biology of this species can inform its conservation, sustainable exploitation, and ex situ propagation.